Effect of Curry Leaf (Murraya koenigii) as Edwardsiellosis Treatment on Gourami Fish (Osphronemus goramy) - Arif Syaifurrisal; Suciyono; Muhammad Browijoyo Santanumurti; Arief Prajitno; Mohammad Fadjar; Farid Mukhtar Riyadi; Annisa Isti Fauziyyah; Agus Pariawan; Muyassar H. Abualreesh (Aquatic Sciences and Engineering)
The primary objective of this study was to explore the potential of Murraya koenigii as a natural alternative to synthetic antimicrobial agents for the treatment of edwardsiellosis in gourami fish (Osphronemus goramy). This research employed a combination of both experimental and descriptive methods. The research followed a two-stage approach. In the first stage, antibacterial compounds were extracted and characterized from M. koenigii leaves, followed by an assessment of their antibacterial activity against Edwardsiella tarda. The second stage involved applying the crude extract of M. koenigii, known for its antibacterial properties, to gourami fish infected with E. tarda. The findings revealed that M. koenigii predominantly contains alkaloids, terpenoids, saponins, flavonoids, and tannins, all of which exhibit antibacterial activity. The application of the crude M. koenigii extract had a substantial impact on the hematological profile of the infected gourami fish. The most effective dose in treating Edwardsiellosis in gourami fish was found to be 600 mg/L, as it significantly improved various hematological parameters, including hematocrit, hemoglobin, erythrocyte count, leukocyte count, lymphocytes, monocytes, and neutrophils. Additionally, histopathological analysis showed improvements in tissue conditions, with lower scores for degeneration, congestion, and necrosis. Furthermore, the survival rate of gourami fish reached its highest at 83.33% when treated with the 600 mg/L dose of M. koenigii extract. These results suggest the potential of M. koenigii as an effective alternative for the treatment of Edwardsiellosis in gourami fish. However, further research is needed to assess the practical application of M. koenigii extract in gourami fish culture.